Silencing of Tumor Necrosis Factor Receptor 1 by siRNA in EC109 Cells Affects Cell Proliferation and Apoptosis - Changhui, Ma (Hindawi Publishing Corporation, 2009)
Tumor necrosis factor receptor 1 (TNFR1) is a membrane receptor able to bind TNF-α or TNF-β. TNFR1 can suppress apoptosis by activating the NF-κB or JNK/SAPK signal transduction pathway, or it can induce apoptosis through a series of caspase cascade reactions; the particular effect may depend on the cell line. In the present study, we first showed that TNFR1 is expressed at both the gene and protein levels in the esophageal carcinoma cell line EC109. Then, by applying a specific siRNA, we silenced the expression of TNFR1; this resulted in a significant time-dependent promotion of cell proliferation and downregulation of the apoptotic rate. These results suggest that TNFR1 is strongly expressed in the EC109 cell line and that it may play an apoptosis-mediating role, which may be suppressed by highly activated NF-κB.